2015 37th Annual International Conference of the IEEE Engineering in Medicine and Biology Society (EMBC) 2015
DOI: 10.1109/embc.2015.7319445
|View full text |Cite
|
Sign up to set email alerts
|

Balance of synaptic and electrotonic connections controls the excitability of networks in biophysical model of epilepsy

Abstract: Recent studies have implicated astrocytes in multiple active roles in neuronal networks. In particular they have been shown to be able to moderate and alter neural firing patterns both in normal and epileptic conditions. In addition, it has been proposed that one of the roles of gap junctions between astrocytes, as well as neurons is in increasing synchronization of neuronal firing and potential epileptogenic effect. In this study we build upon a model of a network that incorporates both pyramidal cells and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Finally, although in this model we included some gap junctions between pyramidal cells and interneurons, many more exist between many cells in the brain, including interneurons, pyramidal cells, and astrocytes, which can have varying effect on both potassium concentrations and epileptogenesis [47]. Our preliminary results on effects of gap junctions in neuro-glial networks have shown that astrocytic gap junctions could help to ameliorate seizure-like states [48], possibly due to increased potassium clearance. Including a more diverse selection of gap junctions in the model could help model the additional role of astrocytes in maintaining excitability balance in neuro-glial networks.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, although in this model we included some gap junctions between pyramidal cells and interneurons, many more exist between many cells in the brain, including interneurons, pyramidal cells, and astrocytes, which can have varying effect on both potassium concentrations and epileptogenesis [47]. Our preliminary results on effects of gap junctions in neuro-glial networks have shown that astrocytic gap junctions could help to ameliorate seizure-like states [48], possibly due to increased potassium clearance. Including a more diverse selection of gap junctions in the model could help model the additional role of astrocytes in maintaining excitability balance in neuro-glial networks.…”
Section: Discussionmentioning
confidence: 99%